2018
DOI: 10.1186/s40536-018-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

How long is the shadow? The relationships of family background to selected adult outcomes: results from PIAAC

Abstract: Background: Ongoing interest in the relationships between family background and adult outcomes is motivated by concerns regarding the intergenerational transmission of advantage/disadvantage. Currently all countries are far from achieving the ideal that all individuals, irrespective of their starting points or their demographic characteristics, are able to accumulate sufficient human capital so that they can achieve success in the workplace and fulfill their responsibilities as family members and as citizens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…taking PIAAC as an example, one topic of interest is the nature of the statistical patterns related to adult incomes. In all countries, even after adjusting for family background, age, cognitive skills, educational attainment, full-time employment, and occupational category, women are less likely (and in some countries markedly so) than men to achieve incomes that place them in the top quartile of the national income distribution (Braun 2018). the consistency of the findings across twentyone OECD countries is striking, but still only suggestive.…”
Section: Technical Issuesmentioning
confidence: 82%
See 1 more Smart Citation
“…taking PIAAC as an example, one topic of interest is the nature of the statistical patterns related to adult incomes. In all countries, even after adjusting for family background, age, cognitive skills, educational attainment, full-time employment, and occupational category, women are less likely (and in some countries markedly so) than men to achieve incomes that place them in the top quartile of the national income distribution (Braun 2018). the consistency of the findings across twentyone OECD countries is striking, but still only suggestive.…”
Section: Technical Issuesmentioning
confidence: 82%
“…that information would come from auxiliary sources such as longitudinal studies or substantively grounded analyses of underlying mechanisms. For example, estimates of gender-related differences in incomes (Braun 2018) should not be interpreted directly as measures of bias in the workplace. Other factors, such as choices people make in trading income for time flexibility, as well as differences in employment histories (e.g., the extent of part-time work or time out of the workforce), may account for some of the observed differences in incomes.…”
Section: Technical Issuesmentioning
confidence: 99%
“…ILSA results are also used for secondary analyses that can uncover patterns of relationships that either directly inform policy or suggest promising directions for further study. Using PIAAC data for OECD countries, Braun (2018) showed that women working fulltime were much less likely than men working full-time to have incomes in the top quartile of the national income distribution, even after controlling for family background, measured cognitive skills, educational attainment, and occupational sector. The degree of disadvantage ranged from modest (United States) to very substantial (Japan, Netherlands).…”
Section: Policy Utilitymentioning
confidence: 99%
“…A practical strategy for conducting analyses that take into account these challenges is illustrated here with a subset of the findings reported by Braun (2018). 1 Braun employed data from an international assessment of adult literacy, the Programme for the International Assessment of Adult Competencies (PIAAC Cycle 1 -Round 1).…”
Section: Introductionmentioning
confidence: 99%
“…The focal outcome that concerns us here is the individual's location in the national income distribution. Braun (2018) investigated the extent to which the strength of the associations between temporally earlier variables were attenuated as more proximal variables were entered. Specifically, interest centered on quantifying the 'long shadow' of demographic characteristics and family background on an individual's labor market success-both as the sole set of predictors and in the presence of more proximal measures of cognitive skills and educational attainment.…”
Section: Introductionmentioning
confidence: 99%